Learners' beliefs on english language learning and their language learning difficulties: the polytechnic scenario / Suria Mokhtar - Mokhtar, Suria (2011)
Beliefs about language learning held by learners can either act as a boost in acquiring and mastering the target language learnt or a big deterrent in this matter. This study focuses on identifying the beliefs held by the final year students of Politeknik Kota Bharu majoring in commerce. Apart from that, this study was also intended to find out what are the difficulties faced by these students during their language learning process. A mix method design was employed whereby a self reported questionnaire based on an adapted Horwitz's (1988) Beliefs About Language Learning Inventory (B ALLI) inclusive of four open-ended questions as a research instrument was used for data collection purposes. Horwitz's BALLI (1988) was adapted with some modifications done to suit the Malaysian context generally and Politeknik Kota Bharu context specifically. The 200 samples chosen based on purposive sampling selected from final semester commerce students comprising of semester five and six were given a set of questionnaire each. An analysis of the quantitative and qualitative data yields the respondents acknowledgement and their belief on the importance of English language in bringing them success in their future career regardless of how difficult and challenging English grammar was to them. Significant relationships between the 'nature of language learning', the 'learning and communication strategies' and the 'motivation and expectation' with the 'difficulty of language learning' were seen from the statistical analysis. It can be concluded that majority of the beliefs held by the respondents acknowledge the notion mastering the English language is important for self development, social status and future career. Understanding the students' beliefs and their language learning difficulties would also enable English teachers to develop better teaching methods for the teaching and learning of English for second language learners. As this study was only limited to the final year students of commerce programmed, it is recommended studies on student beliefs be conducted on students of other programmers as they may have different needs and usage for English language. Much is also needed to investigate relationship between learners' prior learning experience with their current beliefs, problems with the English language that they had faced in their previous learning experience and also their current language experience. By having knowledge on students' beliefs and their language learning difficulties, the data would also help the English language teachers to reshape students' negative beliefs and their expectations about learning.